Fantastic hope - Hamilton, Laurell K.; McCaskey, William (Berkley, 2020)
"A collection of sixteen sci-fi and fantasy stories edited by #1 New York Times bestselling author Laurell K. Hamilton and debut author William McCaskey. A girl who will go to any lengths to save her newborn brother. A woman who is stuck in a continuous loop, reliving her life after being murdered over and over again by the same man. Martyrs who make the ultimate sacrifice for humanity. In this anthology, sixteen authors have weaved together brand-new stories that speak to the darkness and despair that life brings but, above all, the hope that shimmers within it."--